Analisis Faktor Kecerdasan Mahasiswa PGMI STAI Raden Rahmat Ditinjau Dari Teori Multiple Intelligence - Inayati, Isna Nurul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2016)
Study program STAI Raden Rahmat Malang is a primary teacher at levels of Madrasah/ Elementary School hasand four competencies, namely pedagogical, personality, social, and professional. Enactment as a classroom teacher as one of the Islamic Elementary School Teacher’s Education graduates profile is certainly an impact on the competencies required by the prospective graduates. Apart from being required to have a better understanding of the intelligence related to the type of learners, Islamic Elementary School Teacher Education students are required to master all subjects in Islamic Elementary Schools which incidentally have high levels of complexity. Based on such exposure, the study aimed to describe the intelligence of Islamic Elementary School Teacher Education students in STAI Raden Rahmat Malang in terms of the theory of Multiple Intelligence, and then determine the dominant type of intelligence they have. Analysis of the results of this study is expected to be useful for the improvement of the curriculum and the implementation of the study program in Islamic Elementary School Teacher’s Education classes at STAI Raden Rahmat Malang. This study uses a quantitative approach, observational type. Data were collected by questionnaires with respondents 30 students in primary STAI Raden Rahmat Malang. Data were analyzed using descriptive statistics and factor analysis. Based on an analysis tool used determines that the musical intelligence factor cannot be used to analyze the intelligence of students in Elementary School Teacher’s Education and the general type of intelligence of students in Elementary School Teacher’s Education of STAI Raden Rahmat Malang included in the category of social intelligence that consists kinesthetic intelligence, interpersonal, intrapersonal and naturalist intelligence. Keywords: Intelligence, students in primary, Multiple Intelligence